[3-N2-o-C2B10H11][BF4]: a useful synthon for multiple cage boron functionalizations of o-carborane. Issue 9 (14th June 2016) - Zhao, Da; Xie, Zuowei
Abstract : Reaction of [3-N2 - o -C2 B10 H11 ][BF4 ] with various kinds of nucleophiles gives a very broad spectrum of cage B(3)-substituted o -carborane derivatives, 3-X- o -C2 B10 H11 (X = OH, SCN, NH2, NO2, N3, CF3, PO(C6 H5 )2, etc. ), and serves as a simple and efficient method for multiple functionalization of o -carborane. Abstract : A simple and efficient method for selective cage B(3) multiple functionalization of o -carborane is described. Reaction of [3-N2 - o -C2 B10 H11 ][BF4 ] with various kinds of nucleophiles gave a very broad spectrum of cage B(3)-substituted o -carborane derivatives, 3-X- o -C2 B10 H11 (X = OH, SCN, NH2, NO2, N3, CF3, PO(C6 H5 )2, etc ). This reaction may serve as another efficient [ 18 F]-radiolabeling method of carborane clusters for positron emission tomography applications.